Integrated effect of soil tillage implements and weeding intervals on leaf area index and chlorophyll content of maize crop leaves - Luqman; Hussain, Zahid (Journal of Himalayan Earth Sciences, 2021)
The combination of tillage implements and weeding durations is very important for the improvement in the leaf area index and chlorophyll content of fodder maize along with the environment friendly management of the weeds infesting maize crop. In this connection, two field experiments were conducted at the Research Farm of the University of Agriculture Peshawar during the summer seasons of 2016 and 2017. Two tillage implements including mouldboard plough and cultivator as factor A (allotted to main plots) and 14 different weeding durations as factor B (assigned to subplots) were used in a randomized complete plot design with split plot arrangement. Data were recorded on leaf area, leaf area index, number of leaves plant-1, and the chlorophyll content of maize plants. The results indicated that there was a higher leaf area (294 cm2), leaf area index (2.1), leaves count plant-1 (11.7) and chlorophyll content (50.1 SPAD values) in mouldboard plough treatments than in the cultivator treatments. On the other hand, among the weeding intervals, the highest leaf area (377 cm2), leaf area index (2.7), leaves count plant-1 (13) and chlorophyll content (60.3 SPAD values) were achieved in full season weeding treatments, followed by 12 weeks weeding treatments, 10 weeks, 8, 6, 4 and 2 weeks weeding. Moreover, for the interaction of tillage implements and weeding regimes, the leaf area, leaf area index, leaves count plant-1and chlorophyll content were highest in the interaction of mouldboard plough under full season weeding regimes. In conclusion, the interaction of mouldboard plough with full season weeding has been the most successful combination for achieving the best leaf area index and chlorophyll content of maize crop plants